House of Usher - Leeuwen, Evert Jan van (Devil's advocates., 2019)
This study of Roger Corman's House of Usher explores the film's narrative structure and imagery. Evert van Leeuwen shows how the use of specific techniques creates and sustains the atmosphere of gothic decay and situates horror icon Vincent Price's performance in the context of the Romantic misfit and the postwar countercultural antihero.